Diversity Analysis of 15 Hibiscus Accession Based on RAPD Marker - Miranda Ferwita Sari; Aziz Purwantoro (Jurnal Ilmu Pertanian, 2018)
Genus Hibiscus consist of 300 species in tropical and subtropical regions. Indonesia has many species of Hibiscus genus such as Hibiscus rosa-sinensis, kenaf, rosella, waru, sharon, and others. These species have similar flower morphology despite their different benefits. Flower morphology can be use as morphological marker characters to identify the genetic relationship in one genus of Hibiscus. However, morphological markers are less accurate because they are strongly influenced by the environment, requiring quite amount of time, and showing limited and inconsistent diversity. These limitations make researcher chooses molecular markers that are considered more accurate because the material used is plant DNA. One of the most used molecular marker is Random Amplified Polymorphic DNA (RAPD). This study used DNA extraction from the leaf of 15 Hibiscus genus. The next steps were DNA quantification, temperature and primer optimization, DNA amplification with PCR, electrophoresis with agarose gel, and data analysis. The result showed 10 primers operon used for Hibiscus to produce many polymorphic bands. Analysis result showed a high diversity in control population (Hibiscus cannabinus (K1), Hibiscus sabdariffa (K2) Hibiscus mutabilis (K3), Hibiscus syriacus (K4), Hibiscus schizopetalus (K5)) while in Hibiscus rosa-sinensis, the diversity was low especially on the genotypes of flowers with the same color. Molecular marker is a right way to identify the diversity in a population. Control group which consist of Hibiscus cannabinus, Hibiscus sabdariffa, Hibiscus mutabilis, Hibiscus syriacus and Hibiscus schizopetalus has high heterozygosity means control group has high diversity. From the PCA result, grouping in control plants is based on their age (perennial and annual), while in Hibiscus rosa-sinensis the grouping is based on the flowers color. Hibiscus rosa-sinensis is cross pollinated plants caused the position stigma higher than anthers, its prooved by this experiment that varians within population Hibiscus rosa-sinensis higher than among population.